Low Arousing Positive Affect Broadens Visual Attention and Alters the Thought-Action Repertoire While Broadened Visual Attention Does Not - Jäger, Daniel T.; Rüsseler, Jascha (Frontiers in Psychology, 2016)
The Broaden-and-Build Theory states that positive emotions broaden cognition and therefore build personal resources. However, missing theoretical precision regarding the interaction of the cognitive processes involved offers a variety of possible explanations for the mechanisms of broadening and building. In Experiment 1 we tested the causality assumption which states that positive emotions first broaden visual attention which in turn leads to broadened cognition. We examined the effects of a broadened, narrowed or neutral attentional scope of 72 subjects (30 men) on their momentary thought-action repertoire. Results showed that there were no significant differences between groups regarding the breadth or the content of the thought-action repertoire. In Experiment 2 we studied the non-causality hypothesis which assumes a non-causal relationship between cognitive processes. We did so by investigating the effects of negative, neutral, and positive affect on the visual attentional scope of 85 subjects (41 men) in Experiment 2a, as well as on the thought-action repertoire of 85 participants (42 men) in Experiment 2b. Results revealed an attentional broadening effect in Experiment 2a but no differences between groups concerning the breadth of the thought-action repertoire in Experiment 2b. However, a theory driven content analysis showed that positive affect promoted social actions. Thus, our results favor the non-causality assumption. Moreover, results indicate that positive emotions do not target personal resources in general but rather resources associated with social behavior. In conclusion, we argue that the Broaden-and-Build Theory should be refined.